A new application of homotopy perturbation method to the reaction-diffusion Brusselator model - Chowdhury, Md. Sazzad Hossien; Hassan, Talib Hashim; Mawa, S. (Elsevier, 2010)
In this work, an analytical expression for the solution of the the reaction-diffusion Brusselator model is derived by the homotopyperturbation method. The advantage of this work is twofold. Firstly, the homotopy-perturbation method reduces the computational work. Secondly, in comparison with existing techniques, the homotopy-perturbation method is an improvement with regard to its accuracy and rapid convergence. The homotopy-perturbation method has advantage of being more concise for analytical and numerical purposes. The results show the reliability and efficiency of the proposed method.